Ganho genético para produção de grãos em populações precoces nas gerações f2 e f3 de soja - Silva, Carolina Oliveira da (2020)
The advance of the worldwide production of soy is possible due to genetic improvement programs that seek to develop cultivars with high productive potential, resistant to biotic and abiotic stresses. The evaluation of genetic parameters in early generations in plant breeding consists of selecting individuals and progenies in early generations of inbreeding, such as F2 and F3, and thus advancing only progenies with the potential to generate pure productive lines and with superior agronomic characteristics. The objectives of this work were to estimate genetic and phenotypic parameters in populations F2 and F3; evaluate different genotype selection strategies and select progenies to improve agronomic traits and grain production. The experiment was carried out at the Capim Branco experimental farm at the Federal University of Uberlândia, located in Uberlândia - MG. Early populations in the F2 and F3 generations derived from a biparental cross between the parents UFUS 7415 and TMG 7161 RR were evaluated. In the first stage of the experiment, the genetic parameters of 360 individuals in the F2 generation and 150 genotypes of each parent were evaluated. Heritability varied from 4,66 % for number of seeds per pod to 86.06 % for plant height at flowering in the F2 generation.Transgressive segregants were obtained for almost all characters under study, except for APV and NVT. It is possible to infer that the greatest selection gains were obtained for the characters number of nodes at flowering (19.97 %), plant height at maturity (26.08 %) and plant height at flowering (29.68 %), related to grain production. In the second stage of the experiment, 145 genotypes in the F3 generation and their parents were evaluated in a randomized block design with two replications, each experimental unit was constituted by a 1.0 m row with 10 seeds per meter. The genetic parameters, the correlations between characters and the genetic gains obtained by direct and indirect selection and based on the indexes of the Genotype-Ideotype distance and the index of the sum of “ranks” by Mulamba, Mock (1978) were evaluated. Different groups of averages were formed for the characters under study. With direct selection, selection gains ranged from -5.34 % for number of days for flowering to 16.19 % for grain production per row. The genotype- ideotype distance index showed a total selection gain of 40.49 %, while the Mulamba, Mock (1978) sum of ranks index obtained a total gain of 39.35 %, and the gains of selection for cycle characters and characters related to grain production were superior by the sum of “ranks”.